Tools From The "Hat" of an Operational Manager, with an Applied: Case Study - Matei, Denisa Ligia (Archives of Business Research, 2024)
Introduction to Operations Management is an essential starting point for understanding the complexity and importance of effectively managing resources and processes within contemporary organizations. According to Jay Heizer and Barry Render in their seminal work Principles of Operations Management, operations management is defined as the process of designing, managing, and improving processes and systems that create and deliver goods and services. It is a vital component of organizational strategy, having a direct impact on a company's competitiveness and market success. Through operational management, organizations can optimize the use of resources, improve efficiency and provide added value to their customers. We briefly present quantitative forecasting methods, go into detail in a case study with a causal (associative) forecast, then approach the linear regression calculation model. Also, we will estimate pancake sales using the Brown model of exponential leveling, the working tool being QM for Windows. We close the paper by punctually addressing methods of stock optimization by carrying out the case study with the method of uniform price reduction. Finally, we will schematically point out an investment project model for a pancake business.